Physiotherapy through pseudo- competitive games (hardware setup) - Mohamed Namis (2017)
In addition to reducing their muscular pain, the main reason a person goes through physiotherapy is to assist in their recovery of a lost function due to health problems or injury. Physiotherapy is essential so that a person can effectively carry out everyday tasks and improve their quality of life and level of independence.